The evolution of GIS ICT applications for sustainable utilisation and management of natural resources in agriculture and rural development of Gauteng - Malema, Michael (My University, 2015)
The evolution of GIS applications in Gauteng Department of Agriculture and Rural Development (GDARD) was addressed in the study about Rationalisation and Optimisation of Spatial Information Exploration (ROSIE) report which reflects the GIS history in GDARD before 2003. That report revealed that there was a “large degree of duplication, unconsolidated information resources within the department, and non-provision for wider access to spatial information”. This study focuses on the complexity of introducing centralised GIS decision-support ICT applications in GDARD after 2003, with focus on a particular GIS ICT application for GDARD known as the Gauteng Integrated Decision Support (GIDS) system. The purpose of conducting this study was to determine to what extent the adopted strategies, methods and processes are contributing to the attainment of the policy mission for “sustainable utilisation and management of natural resources” in Gauteng. The methodology used reviews GIS usage, skills and access to spatial information i.e. e-service delivery. The data was collected from individuals from GDARD, other Gauteng Provincial Government (GPG) departments, GPG agencies and GDARD stakeholders. The data was analysed using an interpretive qualitative method of research in the context of policy, strategy and operations and their influence on the effectiveness and efficiency of integrated GIS systems. The findings of this study indicate that the stakeholders needs for e-service delivery have not been not fully met. It recommends that the Chief Executive Officers (CEO), Chief Information Officers (CIO) and Chief Financial Officers (CFO) should jointly evaluate, direct and monitor ICT projects to ensure that the major business drivers and benefits like e-services are effectively and efficiently delivered.provision for wider access to spatial information”. This study focuses on the complexity of introducing centralised GIS decision-support ICT applications in GDARD after 2003, with focus on a particular GIS ICT application for GDARD known as the Gauteng Integrated Decision Support (GIDS) system. The purpose of conducting this study was to determine to what extent the adopted strategies, methods and processes are contributing to the attainment of the policy mission for “sustainable utilisation and management of natural resources” in Gauteng. The methodology used reviews GIS usage, skills and access to spatial information i.e. e-service delivery. The data was collected from individuals from GDARD, other Gauteng Provincial Government (GPG) departments, GPG agencies and GDARD stakeholders. The data was analysed using an interpretive qualitative method of research in the context of policy, strategy and operations and their influence on the effectiveness and efficiency of integrated GIS systems. The findings of this study indicate that the stakeholders needs for e-service delivery have not been not fully met. It recommends that the Chief Executive Officers (CEO), Chief Information Officers (CIO) and Chief Financial Officers (CFO) should jointly evaluate, direct and monitor ICT projects to ensure that the major business drivers and benefits like e-services are effectively and efficiently delivered.
Thesis (M.M. (ICT Policy and Regulation))--University of the Witwatersrand, Faculty of Commerce, Law and Management, Graduate School of Public and Development Management, 2014.